2020
DOI: 10.3390/su12072735
|View full text |Cite
|
Sign up to set email alerts
|

Truly Sustainability or Hypocrisy: The Effects of Corporate Sustainable Orientation on Consumers’ Quality Perception and Trust Based on Evidence from China

Abstract: Sustainable initiatives have been widely fulfilled by corporations, which can acquire better reputations by performing environmental, social, and economic responsibilities. However, if a corporation’s propaganda about sustainable orientation is contrary to the actual action, or even does not have a clear orientation, then it may also fall into the reputation of hypocrisy. In this study, from the perspective of consumer behavior and based on the moral responsibility theory of corporate sustainability, we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…Sustainability orientation has a positive association with firms' marketing practices (V at am anescu, Gazzola, Dinc a, & Pezzetti, 2017), thus firms with marketing innovation tools have a more eco-friendly approach (Fiore, Silvestri, Contò, & Pellegrini, 2017). In this vein, sustainability-oriented firms are positively viewed by the customers because it has positive impacts on customer trust, their quality perceptions and satisfaction (Gerdt, Wagner, & Schew, 2019;Liang, Hu, & Meng, 2020). Moreover, previous studies have reported the positive impacts of a firms' sustainability orientation on its legitimating behavior (Reynolds et al, 2018), SSM practices (Shou et al, 2019), carbon strategy, and performance (Moussa, Allam, Elbanna, & Bani-Mustafa, 2020).…”
Section: Macro (Contextual and Environmental)mentioning
confidence: 99%
“…Sustainability orientation has a positive association with firms' marketing practices (V at am anescu, Gazzola, Dinc a, & Pezzetti, 2017), thus firms with marketing innovation tools have a more eco-friendly approach (Fiore, Silvestri, Contò, & Pellegrini, 2017). In this vein, sustainability-oriented firms are positively viewed by the customers because it has positive impacts on customer trust, their quality perceptions and satisfaction (Gerdt, Wagner, & Schew, 2019;Liang, Hu, & Meng, 2020). Moreover, previous studies have reported the positive impacts of a firms' sustainability orientation on its legitimating behavior (Reynolds et al, 2018), SSM practices (Shou et al, 2019), carbon strategy, and performance (Moussa, Allam, Elbanna, & Bani-Mustafa, 2020).…”
Section: Macro (Contextual and Environmental)mentioning
confidence: 99%
“…Consumers have a strong influence on companies with regard to product performance, product safety, and environmental impact, and the companies having direct customer interactions are more likely to adopt environmentally friendly practices [26]. The type of sustainable goals and structure of an organization have implications for customer's sustainable quality perceptions [27].…”
Section: Customer Concern and Corporate Environmentalismmentioning
confidence: 99%
“…We used SPSS 22.0 software to test 427 valid samples following a previous study (Liang et al, 2020(Liang et al, , 2022. These results (Table 2) show that the overall α is 0.902, the Kaiser-Meyer-Olkin (KMO) value is 0.887 and the α of each variable is all greater than 0.6.…”
Section: Measurement Modelmentioning
confidence: 99%